Everyday Practices of Bosnian Muslims (Context: Journal of Interdisciplinary Studies, 2021)
This paper examines certain significant practices and customs used by Bosnian Muslims to manage major life cycle events, both as individuals and collectively. The focus is on what is often termed lived everyday religion rather than on normative structures. While the paper looks at Muslims and how they live their religion, without prejudging how aligned that practice is with Orthodox teachings, any discussion of such practices will naturally touch on ethical dilemmas they face as individuals while doing so.